Recycling for my neighbourhood? Using place identity and social norms to promote pro-environmental behaviour - Lima, M.-L.; Branco, C. (PsyEcology, 2018)
Pro-environmental behaviour has often been studied as being the result of individual or rational decision making, despite the contributions from a more social approach to environmental psychology. This paper presents experimental research addressing the role of social identities and social norms in promoting pro-environmental behaviour. Following the frameworks of Social Identity Theory and Normative Focus Theory, we expect that descriptive social norms will have an impact on behaviour and that social identity will moderate this association. Place identity and descriptive norms regarding pro-environmental behaviour were manipulated in three studies. Self-reported intentions to recycle were assessed, after controlling for past recycling behaviour and environmental identity. The first study (participants: N = 43) showed that the intention of recycling was stronger when descriptive norm was higher. The second (N‍‍‍ = ‍37) and the third (N = 65) studies showed an interesting interaction effect: the salience of social identity was effective when the descriptive social norm was low, and the salience of personal identity promoted recycling when the descriptive social norm was high. These results are expected to stimulate new areas of research in this domain.